Effect of foliar application of panchagavya and banana pseudostem sap on the growth, seed yield and economics of fenugreek - Yonika Saini; P. H. Patel; T. Gangadhara; Priya Chaudhari; Anju Bijarnia (Annals of Agricultural Research, 2022)
A field experiment on loamy-sand soil carried out during the rabi season of 2020-2021 at Sardarkrushinagar, Dantiwada, Gujarat, to study the effect of foliar application of panchagavya and banana pseudostem sap on growth and seed yield of fenugreek. The experiment consisting ten treatments were evaluated in randomized block design with four replications. The results revealed that the growth and yield attributes of fenugreek viz; plant height, nodule weight/plant (fresh & dry), branches/plant, pods/plant, seeds/pod, pod length(cm) and test weight(g) were recorded significantly higher with application of panchagavya @ 4% spray at pre flowering + pod setting being equally effective with panchagavya @ 4% spray at pod setting, whereas, for nodules/plant it was significantly superior over rest. Maximum seed (1438 kg/ha) and haulm (3613 kg/ha) yield were found under the treatment panchagavya @ 4% spray at pre flowering + pod setting followed by panchagavya @ 4% spray at pod setting. The highest gross realization ( 64,746/ha) and net realization (34,259/ ha) were also recorded with application of (treatment T4 ) return panchagavya @ 4% spray at pre return flowering + pod setting stage.